Electrical characterization of lead zirconate titanate prepared by organic solution route - Las, W. C.; Spagnol, P. D.; Zaghete, M. A.; Cilense, M. (Elsevier B.V., 2001)
Two series of lead zirconate titanate (PZT) ceramics with composition Zr/Ti approximate to 53/47 have been prepared by the organic solution route. The effects on the electrical properties of calcination temperature in one series and of sintering time period in the other were examined. Dielectric constant, electrical conductivity and impedance spectroscopy results differed from one series to the other, probably due to differences in structure of the precursor powders, as seen by X-ray diffraction. Tetragonal and rhombohedral phases predominate in the powders used, respectively, in the calcined and sintered series. Physical and electrical behavior of ceramics prepared from predominantly rhombohedral powder suggests the evaporation of PbO. The presence of two semi-circles in impedance plots leads to the association of the low frequency semi-circle to the presence of PbO, which, apparently, was not eliminated from ceramics prepared from predominantly tetragonal powder. (C) 2001 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: dielectric properties; electrical conductivity; impedance; PZT